The Use of Immunohistochemistry, Fluorescence in situ Hybridization, and Emerging Epigenetic Markers in the Diagnosis of Malignant Pleural Mesothelioma (MPM): A Review - Rozitis, Eric; Johnson, Ben; Cheng, Yuen Yee; Lee, Kenneth (Frontiers in Oncology, 2020)
Malignant pleural mesothelioma (MPM) is an aggressive asbestos related disease that is generally considered to be difficult to diagnose, stage and treat. The diagnostic process is continuing to evolve and requires highly skilled pathology input, and generally an extensive list of biomarkers for definitive diagnosis. Diagnosis of MPM requires histological evidence of invasion by malignant mesothelial cells often confirmed by various immunohistochemical biomarkers in order to separate it from pleural metastatic carcinoma. Often when invasion of neoplastic mesothelial cells into adjacent tissue is not apparent, further immunohistochemical testing - namely BAP1 and MTAP, as well as FISH testing for loss of CDKN2A (p16) are used to separate reactive mesothelial proliferation due to benign processes, from MPM. Various combinations of these markers, such as BAP1 and/or MTAP immunohistochemistry alongside FISH testing for loss of p16, have shown excellent sensitivity and specificity in the diagnosis of MPM. Additionally, over the recent years, research into epigenetic marker use in the diagnosis of MPM has gained momentum. Although still in their research stages, various markers in DNA methylation, long non-coding RNA, micro RNA, circular RNA, and histone modifications have all been found to support diagnosis of MPM with generally good sensitivity and specificity. Many of these studies are however limited by small sample sizes or other study limitations and further research into the area would be beneficial. Epigenetic markers show promise for use in the future to facilitate the diagnosis of MPM.